1999
DOI: 10.1111/j.1095-8649.1999.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior residence, aggression and territory acquisition in hatchery‐reared and wild brown trout

Abstract: In an artificial stream environment, established wild brown trout initiated 44% of the mean aggressive acts whilst hatchery-reared trout initiated 34% and introduced wild trout initiated 22%. Established wild fish maintained home stations closer to a point source of feed than did both hatchery-reared and introduced wild conspecifics. Established wild fish were the only group to show a positive mean specific growth rate during the trials. Introduced wild fish showed a slightly negative mean specific growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 21 publications
5
83
0
2
Order By: Relevance
“…Corroborating this assumption, non-parametric tests on microhabitat use, made before and after stocking, showed that there was no evidence of any change in niche characteristics of the native trout. The low impact of the stocked trout on resident populations is also confirmed by the lack of agonistic interactions assessed during snorkel surveys, despite the larger size and more aggressive behaviour normally displayed by stocked trout, as reported by MESA (1991) andDEVERILL et al (1999). Thus, it is possible that the habitat segregation followed by native and stocked fish may be the result of selective segregation rather than competitive interactions (interactive segregation).…”
Section: Discussionmentioning
confidence: 63%
“…Corroborating this assumption, non-parametric tests on microhabitat use, made before and after stocking, showed that there was no evidence of any change in niche characteristics of the native trout. The low impact of the stocked trout on resident populations is also confirmed by the lack of agonistic interactions assessed during snorkel surveys, despite the larger size and more aggressive behaviour normally displayed by stocked trout, as reported by MESA (1991) andDEVERILL et al (1999). Thus, it is possible that the habitat segregation followed by native and stocked fish may be the result of selective segregation rather than competitive interactions (interactive segregation).…”
Section: Discussionmentioning
confidence: 63%
“…CUNJAK et POWER (1986) et CUNJAK (1988 ont montré, pour des juvéniles de saumon (Salmo salar L.), que le début de l'hiver est une période de stress et de mortalité accrue correspondant à l'acclimatation à des conditions environnementales rapidement changeantes. Les études réalisées par BACHMAN (1984) et DEVERILL et al (1999 montrent qu'une des causes de la mortalité supérieure des truites de repeuplement issues de stocks domestiques est l'existence de dépenses énergétiques excessives. b) Une autre hypothèse est l'existence d'une plus forte tendance à la dévalaison pour les truites issues du repeuplement.…”
Section: Dynamique Des Différentes Fractions Dans La Population En Plunclassified
“…In fact, the inefficient behaviours displayed by hatchery-reared fish contributed to a lesser adaptation to wild environment when compared with native trout. For example, higher aggression levels (Deverill et al, 1999), lack of social dominance structures (Jenkins, 1971), lower efficiency at feeding on wild prey (Olla et al, 1994), higher metabolic rates (Ersbak & Haase, 1983) and reduced swimming ability are reported for stocked salmonids. On the other hand, the hatchery-reared fish are more vulnerable to angling and natural predation ( (Ludwig et al, 2002;Jacobsen, 2005) and higher mortality rates are associated near large stocked fish releases (Marnell, 1985).…”
Section: Discussionmentioning
confidence: 99%